A three-dimensional dynamic DNA walker-mediated branching hybridization chain reaction for the ultrasensitive fluorescence sensing of ampicillin. Issue 17 (4th August 2021) - Jiang, Long; Qu, Xiaonan; Sun, Wenyu; Zhang, Manru; Wang, Yeru; Wang, Yu; Zhao, Yijin; Zhang, Fenfen; Leng, Yuning; Liu, Su; Yu, Jinghua; Huang, Jiadong
Abstract : The sensing system is composed of an Nt·Bbvcl-powered DNA walker blocked by the AMP aptamer, hairpin-shaped DNA track probes (TP) and four kinds of metastable hairpin probes as the substrates of bHCR. Abstract : In this study, a novel, rapid and ultrasensitive fluorescence strategy using the three-dimensional (3D) dynamic DNA walker (DW)-induced branched hybridization chain reaction (bHCR) has been proposed for the detection of ampicillin (AMP). The sensing system was composed of an Nt·Bbvcl-powered DNA walker blocked by an AMP aptamer, hairpin-shaped DNA track probe (TP) and four kinds of metastable hairpin probes as the substrates of bHCR, which triggered the formation of the split G-quadruplex as the signal molecule. Due to the reasonable design, the specific binding between AMP and its aptamer activated the DW, and the DW moved on the surface of the gold nanoparticles (AuNPs) with the help of Nt·Bbvcl to produce primer probes (PPs), which induced bHCR. The products of the bHCR gathered two split G-quadruplex sequences together to form one complete G-quadruplex. The formed G-quadruplex emitted a strong fluorescence signal in the presence of thioflavin-T (ThT) to achieve the purpose of detecting AMP. The sensitivity of this method was greatly improved by the use of the 3D DNA walker and bHCR. The split G-quadruplex enhanced the signal-to-noise ratio (SNR). Under the optimal experimental conditions, a good correlation was obtained between the fluorescence intensity of the sensing system and the concentration of AMP ranging from 5 pM to 500 nM with a limit of detection (LOD) of 3.68 pM. Simultaneously, the method has been applied to the detection of antibiotics in spiked milk samples with satisfactory results.